Different origins of two corpora lutea recovered from a pregnant African elephant (Loxodonta africana). (9th July 2017) - Yamamoto, Y; Nagaoka, K; Kamite, Y; Watanabe, G; Allen, T; Stansfield, F; Taya, K
Contents: Elephant ovaries contain multiple corpora lutea (CLs) throughout pregnancy. Two CLs (P‐1 and P‐2) collected from a pregnant African elephant were used to investigate their origin and physiological state in this study. The mRNA expressions of prolactin receptor, CYP11A and inhibin betaB subunit were higher in P‐2 than in P‐1, while LHCGR and inhibin betaA subunit mRNA were higher in P‐1 than in P‐2. Protein expression of cleaved caspase‐3 was detected in P‐1 but not in P‐2. These results suggest different origins for the two CLs in this one pregnant elephant, and we also demonstrated the production of bioactive prolactin by the elephant placenta.